The use of steel rbs to increase ductility of wooden beams. (15th August 2018) - Montuori, R.; Sagarese, V.
Highlights: Possibility of using a steel Reduced Beam Section in a wooden beam. Reduced Beam Sections constitute the dissipative zones of the structure. Beam to column connections can be realized with a partial strength connection. Provided abachi for RBS represent a usefully design tool. Abstract: Reduced Beam Section (RBS) have been introduced, with reference to steel structure, after the 1994 Northridge, CA Earthquake, due to the brittle failure of beam flange-column flange weldments. In the last decades the connections with RBS have been studied both from an analytical point of view and from an experimental point of view. A lot of experimental tests demonstrated that RBS connections designed according to the most modern seismic codes are able to protect the beam to column connection due to the yielding of the adjacent RBS. In this paper, a new idea regarding the use of steel RBS is presented: the possibility of using a steel RBS in a wooden beam. In this case, RBSs should constitute dissipative zones of the structure, leading to a much better seismic behavior of structure. In fact available ductility of steel is much higher if compared to the available ductility of wood. For this purpose, the yielding of RBSs should precede the yielding not only of the beam to column connections, but also of all the intermediate wooden sections. In the present paper a rigorous analysis is developed in order to assure the protection of the beam to column connections and of all intermediate sections of the wooden beam when horizontal forces increase and steel "dog-bones" yield. In other words, the yielding of both "dog-bones" is promoted, leaving all the other sections in elastic range. The role played by vertical loads and by the amount of section reduction are accounted for, and in addition, the possibility that the beam to column connections are realized with a partial strength connection (a connection which is not able to transmit to column the whole plastic moment of the beam) is considered.